Later greek epic and the latin literary tradition further explorations - Carvounis, Katerina; Papaïōannu, Sophia; Scafoglio, Giampiero (De Gruyter, 2023)
The volume offers an innovative and systematic exploration of the diverse ways in which Later Greek Epic interacts with the Latin literary tradition. Taking as a starting point the premise that it is probable for the Greek epic poets of the Late Antiquity to have been familiar with leading works of Latin poetry, either in the original or in translation, the contributions in this book pursue a new form of intertextuality, in which the leading epic poets of the Imperial era (Quintus of Smyrna, Triphiodorus, Nonnus, and the author of the Orphic Argonautica) engage with a range of models in inventive, complex, and often covert ways. Instead of asking, in other words, whether Greek authors used Latin models, we ask how they engaged with them and why they opted for certain choices and not for others. Through sophisticated discussions, it becomes clear that intertexts are usually systems that combine ideology, cultural traditions, and literary aesthetics in an inextricable fashion. The book will prove that Latin literature, far from being distinct from the Greek epic tradition of the imperial era, is an essential, indeed defining, component within a common literary and ideological heritage across the Roman empire
Keywords: Quintus -- Smyrnaeus -- ca. 4. Jh. -- Posthomerica; Nonnus, Panopolitanus; Orphica. Argonautica; Quintus, Smyrnaeus; Triphiodorus; Griechisch; Epos; Latein; Aufsatzsammlung